AVALIAÇÃO DE UM PROGRAMA DE PADRONIZAÇÃO DA LIMPEZA E DESINFECÇÃO DE SUPERFÍCIE EM UNIDADE PEDIÁTRICA - LUCAS DE OLIVEIRA BERNARDES (2021)
Cleaning and disinfecting the environment helps to prevent infections, helping to minimize the risk of spreading pathogens. Despite this, there are few studies regarding environmental contamination in pediatric inpatient units. From this perspective, this study sought to assess the impact of a Surface Cleaning and Disinfection Standardization Program (PPLDS) in a pediatric inpatient unit. The study was carried out in three stages: step I - situational diagnosis of the surface cleaning and disinfection process (LDS); stage II - implementation of the PPLDS; stage III - evaluation after 2 months after program implementation. The following methods were used for monitoring: visual inspection, counting of Colony Forming Units (CFU) and quantification of Adenosine Triphosphate (ATP). At the end of each stage, 192 evaluations were obtained. At the end of the three stages, 576 evaluations were obtained, considering the three monitoring methods. The results showed efficiency in the LDS process in the three stages of the study. In step I, four surfaces showed statistically significant results by the ATP method and two surfaces by the microbial count (CFU). In stages II and III, all surfaces presented statistically significant results (P<0.05) by both evaluated methods. As for visual inspection, only the bathroom door handle (step I: P=0.041; step III: P=0.007) and the toilet flush trigger (step I: P=0.026; step III: P=0.007) were approved. The analysis of the ROC curves showed the presence of statistical significance in the relationship between the methods of quantification of ATP (P=0.024) and microbial count (P=0.037) in relation to the gold standard of visual inspection. The ATP method returned a sensitivity of 78.6%, showing this percentage as the probability of this technique to correctly identify a clean surface. When related to the gold standard of visual inspection, this methodology can be considered adequate to parameterize the microbiological quality of a hospital surface. It is suggested that surfaces that exhibit ATP below 108 RLU may be considered approved. The microbial count showed a sensitivity of 85.7%, showing high sensitivity in evaluating a hospital surface as clean. It is suggested that the implementation of PPLDS should be carried out continuously and permanently, with the offer of feedback, standardization of practices and monitoring of the process. Keywords: Hospital Housekeeping. Infection Control. Environmental Monitoring. Pediatrics.